Production by five selected molds of cellulose and xylanase for saccharifying corn cobs - Matanguihan, R.M; Del Rosario, E.J (1988)
Cellulase and xynalase activities of tricjoderma reesi NRRL 11460 (T.r.11460). Aspergillus niger NRRL 330 (A.n. 330), Aspergillus niger NRRL 337 (A.n. 337), Penecillium 3060 (P,3060) and penecillium funiculosum 3116 (P.f. 3116) were evaluated in shake-flask and stirred-fermenter cultures using 2% w/v ground corn cobs as substrate. A.n. 330 gave the highest xylanse volumetric activity and productivity of 86.8 IU/ml and 904 IU/I-h, respectiverly. P.3060 produced the highest filter paper activity of 0.459 IU/ml white T.r. 11460 yielded the highest filter paper productivity of 5.2 IU/1-h, A.n. 330 gave the highest B-glucosidase volumetric and specific activities of 1.13 IU/ml and 1.29 IU/mg, respectively, when grown in a stirred-tank fermenter. Saccharification of ground corn cobs using enzyme preparations from T.r. 11460 A.n. 330 and P.f. 3116 demonstrated that P.f. 3116 cellulase had the highest reducing sugar yield of 8.59 mg/ml and saccharification value of 17.2% based on initial weight of the dry substrate. An increase in sachharification was observed using mixed enzyme extracts from T.r. 11460 and P.f. 3116 at 3.7 ratio (v/v) as well as from T.r. 11460 and A.n. 330 at 7:3 ratio (v/v). The saccharification value using T.r. 11460 cellulase increased by about six-fold to 65.3% using corn cobs which had been presented with NaOH-Ethanol. The hydrolysate contained 32.7 mg/ml reducing sugars consisting of xylose, glucose and cellob.